2014
DOI: 10.1590/s1808-18512014130200413
|View full text |Cite
|
Sign up to set email alerts
|

Up-to-date thromboprophylaxis in elective spinal surgery. A systematic review

Abstract: Deep vein thrombosis (DVT) and pulmonary embolism (PE) present a high incidence after surgery, posing a high risk in surgical practice. Although a consensus does exist on thromboprophylaxis in orthopedic surgery, this topic remains controversial in regard to spinal surgery. In this current paper, we review and discuss the different forms of prophyilaxis presented in literature, in order to develop guidelines on prophylactic measures in spinal surgery, improving patient´s outcomes and reducing any medical/legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
(23 reference statements)
0
0
0
Order By: Relevance
“…Overall, the data produced by our study were close to those found in diverse publications in the literature. [26][27][28][29] One of the biases of the present study was the scarcity of prospective randomized clinical trials for analysis. In addition, it was not possible to perform an independent analysis of each outcome, such as DVT, PTE, and epidural hematoma, due to the small number of cases, so the forest plot graphs were not divided by outcome.…”
Section: Discussionmentioning
confidence: 94%
“…Overall, the data produced by our study were close to those found in diverse publications in the literature. [26][27][28][29] One of the biases of the present study was the scarcity of prospective randomized clinical trials for analysis. In addition, it was not possible to perform an independent analysis of each outcome, such as DVT, PTE, and epidural hematoma, due to the small number of cases, so the forest plot graphs were not divided by outcome.…”
Section: Discussionmentioning
confidence: 94%